Knowledge, Attitude and Practices Regarding Electronic Waste (e-waste) Management Among Users of Electronic Equipments Living in Lucknow City - Kariwala, Peeyush; Kandpal, Sunil Dutt; Dixit, Sumeet; Singh, Arvind Kumar; Pathak, Anurag; Singh, Shikhar (Indian Journal of Community Health, 2023)
Background: Contemporary society has led to the increasing use of electronic equipment that is very much responsible for the burden of electronic waste (e-waste). E-waste contains very hazardous substance that harms health and environmental conditions. There is no delicate mechanism for the management of e-waste in Lucknow city, Uttar Pradesh. This study assessed knowledge, practice, and awareness of e-waste management among residents of this city. Material and methods: The study was conducted amongst users of electronic equipment living in the Lucknow City of Uttar Pradesh. The study was a Cross-sectional descriptive study. Multi-stage random sampling was done for the selection of participants for the study. A predesigned and pretested questionnaire was administered in a single setting for all phases. The total optimum sample size is 700 individuals who participated in the study. Data were entered in MS Excel 2016 and descriptive statistics such as frequencies and percentages were calculated, applying the chi-square test for association using R-4.2.1 Statistical software. Aim and objectives: To assess the knowledge, attitude and practices regarding the management of electronic waste among users of electronic equipment residing in Lucknow city. Results: Only 37% of users are aware that e-waste adversely affects health. Only 34.3% of users knew that e-waste should be given to the seller or manufacturer for recycling while rest told that it should be stored at home, sold to a scrap dealer, or disposed with normal waste. 87.3% users are not aware about e-waste govt guidelines. In the current study electronic and print media like television, radio and news paper were not found to be source of information for e-waste disposal. Conclusion: Education regarding the ill effects of e-waste is essential for people and awareness of proper disposal of e-waste is the need of the hour. Electronic and print media as well as companies producing electronic equipment should play a significant role to awaken the respondent about the disposal of e-waste.